Academic Senate Minutes 2009-10-15 - Academic Senate:::::::::
Agenda approved. Minutes of 9/17/09 approved. Update on WASC. By-Law Revision: Change to Charge of the Student Affairs Committee – First Reading. Chair-Elect Report. EPC Report. FSAC Report. APC Report. Resolution recognizing the work of the Ad-Hoc Diversity Committee approved. CFA Report. Staff Representative Report. President's Report – R. Armiñana. Provost Report. Vice President of Administration and Finance Report. Vice President of SAEM Report. Associated Students Report. Statewide Senators Report. Diversity Discussion. Motion that the Academic Senate strongly recommend to Provost the hiring of a Diversity Coordinator for Academic Affairs postponed to next meeting.